2018
DOI: 10.2340/00015555-2795
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Low Grade Systemic Inflammation and Skin Diseases: A Cross-sectional Survey in the Northern Finland Birth Cohort 1966

Abstract: Low grade inflammation is associated with many noncommunicable diseases. The association between skin diseases in general and systemic inflammation has not previously been studied at the population level. A whole-body investigation on 1,930 adults belonging to Northern Finland Birth Cohort 1966 was performed and high sensitive C-reactive protein (CRP) level was measured as a marker of low grade inflammation in order to determine the association between low grade inflammation and skin diseases in an unselected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
4
23
0
1
Order By: Relevance
“…Both clinical and experimental studies have confirmed the important role of inflammation in the pathogenesis of rosacea [ 31 ]. A cross-sectional study found that hs-CRP was higher in patients with rosacea than in those with no skin disease ( p = 0.001) [ 32 ]. All these indicate that, in analogy to psoriasis [ 33 ], the low-grade inflammation in rosacea might be systemic.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and experimental studies have confirmed the important role of inflammation in the pathogenesis of rosacea [ 31 ]. A cross-sectional study found that hs-CRP was higher in patients with rosacea than in those with no skin disease ( p = 0.001) [ 32 ]. All these indicate that, in analogy to psoriasis [ 33 ], the low-grade inflammation in rosacea might be systemic.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of onychomycosis are associated with paronychia, a periungual inflammation [15,16]. Moreover, some studies suggested that low grade systemic inflammation may be associated with onychomycosis as well [17]. The inflammatory response involves an oxidative stress as an injury mechanism [18].…”
Section: Introductionmentioning
confidence: 99%
“…factors, 3,8 gluco-metabolic disturbances including insulin resistance related to systemic low-grade inflammation in patients with AD, 9,10 and possibly use of topical and systemic corticosteroids. 11 Systemic low-grade inflammation (determined by circulating inflammatory markers), as observed in some patients with AD, is a risk factor for insulin resistance and the development of type 2 diabetes.…”
mentioning
confidence: 99%